Feasibility and Morbidity for the Use of MR-Guided Laser-Induced Thermotherapy for the Treatment of Skull Base Tumors: A Report of Three Cases - Lawrence, Jesse D.; Marsh, Robert (Journal of Neurological Surgery Reports, 2023)
Background Laser-induced thermotherapy (LITT) is a minimally invasive technique that has been demonstrated as an effective treatment of many pathologies; however, it has never been investigated for the use in skull base tumors.Case Series Three patients underwent LITT for treatment of skull base meningiomas. All three patients were determined to be poor candidates for open resection. Each patient was treated with a single laser fiber. Postoperative imaging confirmed ablation zones along the tract of the catheter in all three patients. Ablation zones were estimated to be 9 to 20% of the intended to treat tumor volume. Two of three treated patients suffered cranial nerve injury following the procedure with one patient diagnosed with neurotrophic keratitis and one patient with symptoms consistent with anesthesia dolorosa.Conclusion LITT is a technically feasible, minimally invasive treatment modality for skull base lesions. Significant risk to cranial nerves and small ablation zones afforded by a single cannula placement proposes serious obstacles. Further investigation is warranted prior to using this technique outside of a palliative indication.
Keywords: laser interstitial thermal therapy; meningioma; minimally invasive; operative feasibility; skull base tumor